First report of avocado tree wilt by Pythium sp. amazonianum in Mexico - Ochoa Fuentes,Yisa M. (Pontificia Universidad Católica de Chile. Facultad de Agronomía e Ingeniería Forestal, 2018)
Abstract In August and September 2014, different avocado orchards (Persea americana Mill. Var. Hass) were sampled in four municipalities (Tancítaro, Uruapan, San Juan Nuevo Parangaricutiro and Peribán) of the “Franja aguacatera” in Michoacan State, Mexico. Samples were collected from avocado trees showing symptoms of the “Tristeza del aguacate” disease. Strains of Pythium sp. were obtained consistently from symptomatic tissue isolated in the selective medium V8®-Agar-PARPH. Morphological identification was made through taxonomic keys, and molecular identification was obtained by sequencing Internal Transcribed Spacer (ITS) gene. Koch's postulates were corroborated by pathogenicity tests carried out on P. americana seedlings with six true leaves, identifying the strain of P. sp. amazonianum as the causal agent of the “Tristeza del aguacate” disease. This is the first report that associates the “Tristeza del aguacate” with P. sp. amazonianum in Michoacan, Mexico.